The Encyclopedia of Applied Linguistics 2012
DOI: 10.1002/9781405198431.wbeal0932
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Transfer

Abstract: As resourceful human beings, when we embark on a task for the first time, we resort, consciously or unconsciously, to our previous knowledge and experience in order to accomplish the task as efficiently as possible. This also applies to second (or third or other) language acquisition/learning scenarios: When we learn a new language, we already know, at least, a first language and have a wealth of world experience and information that will necessarily play a role in the acquisition and use of the new language. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Consequently, Schmidt, together with other authors, such as Thomas (1983) or Richards and Sukwiwat (1983) among others claim that a direct approach to the teaching of the pragmatics of the L2 is compulsory. Bou-Franch (1998) believes that "if the nonnative speakers are consciously aware of the pragmalinguistic and sociopragmatic similarities and differences between their native and target languages, then negative outcomes of transfer will most probably be inhibited" (p. 5). Therefore, teachers are responsibility for providing the students with the necessary tools to help them make the appropriate pragmalinguistic and sociopragmatic decisions in the target language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Schmidt, together with other authors, such as Thomas (1983) or Richards and Sukwiwat (1983) among others claim that a direct approach to the teaching of the pragmatics of the L2 is compulsory. Bou-Franch (1998) believes that "if the nonnative speakers are consciously aware of the pragmalinguistic and sociopragmatic similarities and differences between their native and target languages, then negative outcomes of transfer will most probably be inhibited" (p. 5). Therefore, teachers are responsibility for providing the students with the necessary tools to help them make the appropriate pragmalinguistic and sociopragmatic decisions in the target language.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, contrastive analysts believed that the L1 interfered with L2 learning. The CAH suggested that where two languages were different, there would be negative transfer or interference since learners would experience difficulty that would result in the production of errors; and that where two languages were similar, there would be positive transfer since learning would be facilitated and no errors would result (Franch, 1998). Franch continued that this led to different ways of accounting for the role of the first language in target language.…”
Section: Historical View Of Language Transfermentioning
confidence: 99%
“…Some scholars insist that generally transfer can be explained through transferring concepts and ways thoughts are presented in different languages (e.g., Arran, 2005;Bou Franch, 1998;Heij, Hooglander, Kerling & Velde ,1996;Jarvis, 2011;Pavlenko, 2000;andVon Stutterheim, 2003, 2005-the last is cited in Ellis, 2008). In the present study, the researcher found out that, such inattentions led to the use of discursive transfer, pragmatic transfer, conceptual transfer, and sociolinguistic transfer which comprises 43.18% of all the kinds of transfer used in this study.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%
“…As has been pointed out earlier, the field responsible for how L2 speakers develop, comprehend, and produce pragmatic patterns is called ILP, with the generalization being that native speakers and L2 learners differ as to how they use their pragmatic knowledge (Ellis, 1994;Kasper and Rose, 1999, amongst others). This apparent mismatch results in Pragmatic Transfer (Bou-Franch, 1998), as a result of L2 learners falling back on their L1 pragmatics iii to comprehend and produce the pragmatics of L2.…”
Section: Pragmatic Competence and Slamentioning
confidence: 99%